2022
DOI: 10.3390/antiox11081570
|View full text |Cite
|
Sign up to set email alerts
|

Improving Skin Carotenoid Levels in Young Students through Brief Dietary Education Using the Veggie Meter

Abstract: The antioxidant and anti-inflammatory effects of carotenoid have been determined to aid in the prevention of a wide range of oxidative disorders, arteriosclerosis, obesity, and various types of cancers. In order to keep high carotenoid levels in the body, much of the vegetable and fruit (V/F) intake is mandatory. However, the actual intake of V/F is not enough in many countries. The aim of this study was to assess whether brief dietary education using the Veggie Meter (VM) that could measure skin carotenoid (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…To date, the intake of FV is evaluated by self-reported FV intake or by measuring the blood carotenoid levels via an invasive and expensive liquid chromatography/mass spectrometry-based analytic method [23,52]. The use of the Veggie Meter ® has been already described as a validated and non-invasive method for skin carotenoid detection, which accurately reflects the FV intake [25,33,34,53]. Therefore, it represents an important tool for an objective measurement of FV intake to overcome bias associated with self-reported questionnaires, allowing us to easily analyze the FV intake in community-based settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the intake of FV is evaluated by self-reported FV intake or by measuring the blood carotenoid levels via an invasive and expensive liquid chromatography/mass spectrometry-based analytic method [23,52]. The use of the Veggie Meter ® has been already described as a validated and non-invasive method for skin carotenoid detection, which accurately reflects the FV intake [25,33,34,53]. Therefore, it represents an important tool for an objective measurement of FV intake to overcome bias associated with self-reported questionnaires, allowing us to easily analyze the FV intake in community-based settings.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the number of carotenoids in the skin is highly correlated with the serum carotenoid concentration and reflects the FV dietary intake in the previous 2-4 weeks [25]. Thus, Veggie Meter ® represents a feasible, reliable, and potentially valid measure of FV consumption [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies 27 , 47 51 clarified the association between fruit and vegetable intake and SC levels measured by VM and some interventional studies 52 , 53 revealed that VM accurately detects differences in carotenoid intake through diet. In our previous study 54 , informing participants of their VM scores has proven effective in motivating fruit and vegetable intake, and repeated measurements have increased SC levels. In addition to these nutritional approaches, SC level identification as an effective measure for preventing various diseases would serve as a valuable indicator in nutritional guidance towards a diet beneficial for disease prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A is essential for the proper function of the eyes and brain, as well as reproduction and other vital activities in the human body; thus, the significance of carotenoids in human nutrition is an indisputable fact. Numerous studies corroborate the multiple positive health effects that a diet rich in carotenoids could offer, from prevention against different types of cancer to protection against depression [3,4]. In this framework, the Food and Agricultural Organization (FAO) and World Health Organization (WHO) have already included several carotenoids in the Codex Alimentarius as safe additives permitted for use in foods.…”
Section: Introductionmentioning
confidence: 92%